Inhibition of hepatocyte nuclear factor 1β contributes to cisplatin nephrotoxicity via regulation of nf‐κb pathway. Issue 6 (29th January 2021) - Zhang, Yan; Hao, Jielu; Du, Zijun; Li, Peiyao; Hu, Jinghua; Ruan, Mengna; Li, Shulian; Ma, Yuanfang; Lou, Qiang
Abstract: Cisplatin nephrotoxicity has been considered as serious side effect caused by cisplatin‐based chemotherapy. Recent evidence indicates that renal tubular cell apoptosis and inflammation contribute to the progression of cisplatin‐induced acute kidney injury (AKI). Hepatocyte nuclear factor 1β (HNF1β) has been reported to regulate the development of kidney cystogenesis, diabetic nephrotoxicity, etc However, the regulatory mechanism of HNF1β in cisplatin nephrotoxicity is largely unknown. In the present study, we examined the effects of HNF1β deficiency on the development of cisplatin‐induced AKI in vitro and in vivo. HNF1β down‐regulation exacerbated cisplatin‐induced RPTC apoptosis by indirectly inducing NF‐κB p65 phosphorylation and nuclear translocation. HNF1β knockdown C57BL/6 mice were constructed by injecting intravenously with HNF1β‐interfering shRNA and PEI. The HNF1β scramble and knockdown mice were treated with 30 mg/kg cisplatin for 3 days to induce acute kidney injury. Cisplatin treatment caused increased caspase 3 cleavage and p65 phosphorylation, elevated serum urea nitrogen and creatinine, and obvious histological damage of kidney such as fractured tubules in control mice, which were enhanced in HNF1β knockdown mice. These results suggest that HNF1β may ameliorate cisplatin nephrotoxicity in vitro and in vivo, probably through regulating NF‐κB signalling pathway.